2018
DOI: 10.1155/2018/6291719
|View full text |Cite
|
Sign up to set email alerts
|

Optimism, Positive and Negative Affect, and Goal Adjustment Strategies: Their Relationship to Activity Patterns in Patients with Chronic Musculoskeletal Pain

Abstract: Objective Activity patterns are the product of pain and of the self-regulation of current goals in the context of pain. The aim of this study was to investigate the association between goal management strategies and activity patterns while taking into account the role of optimism/pessimism and positive/negative affect. Methods Two hundred and thirty-seven patients with chronic musculoskeletal pain filled out questionnaires on optimism, positive and negative affect, pain intensity, and the activity patterns the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 77 publications
7
33
0
Order By: Relevance
“…Negative Associations: Three negative associations were reported. Goal disengagement was associated with increased depression in participants with multiple sclerosis when accompanied by low reengagement (Neter et al, 2009); and with increased negative affect and activity avoidance in participants with chronic pain who scored high on pessimism (Esteve et al, 2018). A negative association was found between goal reengagement and adjustment in people with lower limb amputation (Coffey et al, 2014a).…”
Section: Synthesis Of the Goal Adjustment Literaturementioning
confidence: 95%
See 1 more Smart Citation
“…Negative Associations: Three negative associations were reported. Goal disengagement was associated with increased depression in participants with multiple sclerosis when accompanied by low reengagement (Neter et al, 2009); and with increased negative affect and activity avoidance in participants with chronic pain who scored high on pessimism (Esteve et al, 2018). A negative association was found between goal reengagement and adjustment in people with lower limb amputation (Coffey et al, 2014a).…”
Section: Synthesis Of the Goal Adjustment Literaturementioning
confidence: 95%
“…Psychological interventions: Ten studies suggested six psychological interventions or approaches to support goal adjustment. These were (i) cognitive behavioural therapy (or cognitive approaches) (Esteve et al, 2018;Johnson et al, 2012;Schroevers et al, 2011;Schrooten et al, 2012;Van Damme et al, 2016); (ii) acceptance and commitment therapy (Ciere et al, 2017;Coffey et al, 2014a;Schrooten et al, 2012;Thompson et al, 2013); (iii) motivational interviewing (Hart & Evans, 2006;Johnson et al, 2012;Schrooten et al, 2012); (iv) mindfulness (Schroevers et al, 2008(Schroevers et al, , 2011Schrooten et al, 2012); (v) mental contrasting (Hart & Evans, 2006) and (vi) clarification orientated interventions (Schrooten et al, 2012). All suggestions were made in discussion of study findings or relevant literature, rather than empirical evidence of effectiveness of any particular psychological intervention.…”
Section: Synthesis Of the Goal Adjustment Literaturementioning
confidence: 99%
“…These factors are shown to be significantly associated with greater active coping skills, which may help people with chronic pain to respond to pain with more adaptive thoughts, optimistic self-statements, goal setting, and activity pacing behaviors [ 26 , 27 , 28 ]. Pain acceptance, pain self-efficacy, and optimism have also all been shown to be associated with less disability, pain, disease activity, distress, and medication use [ 19 , 20 , 29 , 30 , 31 ], as well as with greater positive affect, well-being, hope, and treatment adherence behaviors [ 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Buckingham and Richardson (Buckingham & Richardson, 2020 ) relate the level of optimism in individuals to their ability to accept adverse situations, interpreting and assigning meaning to the situation in order to maintain engagement in important life activities. Esteve et al (Esteve et al, 2018 ) found higher levels of optimism to be associated with individuals’ ability to persist and be flexible with their goals, which is in turn related to task persistence and lower activity avoidance despite the adverse situation.…”
Section: Discussionmentioning
confidence: 99%